Heavy metal distribution and contamination status in the sedimentary environment of Cochin estuary. Issue 2 (30th June 2017) - Salas, P.M.; Sujatha, C.H.; Ratheesh Kumar, C.S.; Cheriyan, Eldhose
Abstract: Heavy metals (Fe, Mn, Cr, Zn, Ni, Pb, Cu, Co and Cd) in the surface sediments of Cochin estuary, Southwest coast of India were analyzed to understand the spatio-temporal variation and contamination status via six sampling campaigns. Pollution indices like enrichment factor, geoaccumulation index and pollution load index inferred that the sediments of the northern arm of the estuary exhibited severe trace metal accumulation. Numerical sediment quality guidelines were applied to assess adverse biological effects of the trace metals, suggesting that occasional biological effect may occur due to Cr, Cu, Ni and Pb. Correlations between metals, organic carbon, silt and clay suggested that both fine grained sediment and organic matter were important carriers for these metals. Multivariate statistics indicated that the sources of Cu and Ni resulted primarily from natural weathering processes, whereas enriched levels of Cd, Cr, Zn and Pb were mainly attributed to anthropogenic activities. Highlights: Spatial variations of metal enrichment were monitored in the Cochin estuarine sediments. Cu and Ni were enriched by natural weathering processes. Cd, Cr, Zn and Pb were mainly attributed to anthropogenic activities.